Bioengineered Breast: Concept, Technique, and Preliminary Results. Issue 2 (February 2016) - Maxwell, G. Patrick; Gabriel, Allen
Abstract : Summary: Breasts reconstructed with implants, following mastectomy, lack the soft-tissue envelope of natural breasts. Further implant-related complications such as implant visibility, rippling/wrinkling, and/or hollowing/depression of the skin that often appear in the vicinity of the upper pole may be attributed to soft-tissue deficits. To address these shortcomings, the authors have developed the "bioengineered breast" concept that uses a combination of biological matrix and/or autologous fat grafting at the upper pole to augment the soft-tissue volume of breasts at the second stage of a two-stage breast reconstruction procedure. Enhancing the soft-tissue cover not only supplements volume and shape but further alters how the recipient's host tissue responds to the foreign body implant. The authors have used the bioengineered breast concept in over 500 reconstructions, with good outcomes and low complication rates. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V. Abstract : Supplemental Digital Content is available in the text.Video Discussion by Maurice Nahabedian, M.D., is Available Online for this Article.